2012
DOI: 10.3748/wjg.v18.i32.4308
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of magnifying colonoscopy in the diagnosis of serrated polyps

Abstract: We suggest that this system could be a good diagnostic tool for SSA/Ps using magnifying colonoscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
3
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 37 publications
(48 reference statements)
2
36
3
2
Order By: Relevance
“…In this study, only one lesion (1.3%) presented a type II pit pattern, suggestive of a non-neoplastic lesion, however, after endoscopic resection, it was revealed to be a sessile serrated adenoma, a lesion that could be mistaken for a hyperplastic lesion at colonoscopy (10) . Among the five lesions with type V pit pattern, histology showed one adenoma with high-grade dysplasia, three intramucosal carcinomas and one invasive carcinoma, which was surgically treated later.…”
Section: Discussioncontrasting
confidence: 54%
“…In this study, only one lesion (1.3%) presented a type II pit pattern, suggestive of a non-neoplastic lesion, however, after endoscopic resection, it was revealed to be a sessile serrated adenoma, a lesion that could be mistaken for a hyperplastic lesion at colonoscopy (10) . Among the five lesions with type V pit pattern, histology showed one adenoma with high-grade dysplasia, three intramucosal carcinomas and one invasive carcinoma, which was surgically treated later.…”
Section: Discussioncontrasting
confidence: 54%
“…With regard to the differential diagnosis, the specificity and PPV of the Type II-O pit pattern were sufficient, whereas the sensitivity and NPV were not. These results are similar to those reported previously 11,19 . However, in the present study, VMVs had lower diagnostic accuracy than those reported by Uraoka et al 12 .…”
Section: Discussionsupporting
confidence: 93%
“…Согласно результа там, полученным М. Агаповым и соавт., и IIО тип кишечных ямок, и налет муцина на поверхности об разования обладают относительно низкой чувстви тельностью и высокой специфичностью при диф ференциальной диагностике зубчатых аденом от гиперпластических полипов, составляя соответ ственно 60 и 97% [42]. Другие авторы сообщают о более высокой чувствительности (84%) и более низ кой специфичности (86%) типа IIО кишечных ямок при дифференциальной диагностике зубчатых аденом от гиперпластических полипов [45].…”
Section: доказательная гастроэнтерология 4 2016unclassified